Pengaruh Model Problem Based Learning Terhadap Kemampuan Literasi Sains Biologi SMA - Fani Fenty Aradia; Rahmadhani Fitri; Helendra Helendra (Institut Agama Islam Negeri Kerinci, 2023)
The purpose of this study was to analyze the effect of the Problem Based Learning on high school biology science literacy skills. This research is a type of quantitative research with a literature review. The data for this study came from an analysis of 5 national articles published online. The journals used as references are national journals published from 2017 to 2022. Search for samples to serve as research data through the Google Scholar, Eric, and Library of Indonesia e-resources databases. The sample in this study were high school biology students. The data generated to be used as a research sample is associated with the Problem Based Learning for scientific literacy. The results showed that the Problem Based Learning able to improve high school Biology science literacy skills.